The Influence of Using Prezi Application on the Learning Outcomes of Indonesian Language Lessons for Eighth Grade Students at SMP Negeri 2 Baranti - Andi Muh. Farhan; Usman M; Hasanuddin Hasanuddin; Syamsunir Syamsunir (Universitas Muhammadiyah Enrekang, 2025)
This study aims to identify the effect of using Prezi media on the learning outcomes of eighth-grade students in Indonesian language lessons at SMP Negeri 2 Baranti. With a total population of 99 students, the researcher applied cluster sampling technique to determine the sample. Two classes were selected and divided into an experimental group and a control group. Data collection was carried out through two stages of testing, namely testing on the control group and testing on the experimental group. The findings of the study indicate that the use of Prezi media has a positive impact on improving students' learning outcomes. This is evident from the significant difference between the average scores of the experimental group (92.00) and the control group (69.75). Therefore, it can be concluded that the use of Prezi media effectively enhances students' learning outcomes in Indonesian language lessons.